2019
DOI: 10.3340/jkns.2019.0008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Allogenous Bone Graft Collapse in Two-Level Anterior Cervical Discectomy and Fusion

Abstract: Objective Anterior cervical discectomy and fusion (ACDF) is commonly used surgical procedure for cervical degenerative disease. Among the various intervertebral spacers, the use of allografts is increasing due to its advantages such as no harvest site complications and low rate of subsidence. Although subsidence is a rare complication, graft collapse is often observed in the follow-up period. Graft collapse is defined as a significant graft height loss without subsidence, which can lead to clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…16 Furthermore, Woo et al reported that the graft collapse rate of cortico-cancellous allograft reached 28.8% when significant collapse was assessed by a decrease in disc height of > 30%. 12 However, these reports did not demonstrate whether graft failure, including resorption or fracture, can affect bone union, subsidence, and lordosis restoration.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…16 Furthermore, Woo et al reported that the graft collapse rate of cortico-cancellous allograft reached 28.8% when significant collapse was assessed by a decrease in disc height of > 30%. 12 However, these reports did not demonstrate whether graft failure, including resorption or fracture, can affect bone union, subsidence, and lordosis restoration.…”
Section: Discussionmentioning
confidence: 92%
“…In their retrospective study, Woo et al showed that intraoperative distraction of > 37% from the preoperative disc height increases the chance of allograft failure. 12 Moreover, increased interbody spacer height has been reported as a risk factor for subsidence. 26 Finally, since logistic regression analysis in the present study showed that an increased number of surgical levels are risk factors for allograft failure, special care while applying anterior plating or bone graft would be needed for multilevel surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implant-related complications, such as graft failure, subsidence and screw pullout are major concerns in ACDF-only surgeries. Graft collapse has been reported to occur at 28.8% [ 18 , 19 ]. The risk of subsidence with stand-alone cage or allospacer still remain as one of the main complications with this technique.…”
Section: Discussionmentioning
confidence: 99%